Mycobacterial DnaB helicase intein as oxidative stress sensor. Issue 1 (December 2018) - Kelley, Danielle; Lennon, Christopher; Li, Zhong; Miller, Michael; Banavali, Nilesh; Li, Hongmin; Belfort, Marlene
Abstract Inteins are widespread self-splicing protein elements emerging as potential post-translational environmental sensors. Here, we describe two inteins within one protein, theMycobacterium smegmatis replicative helicase DnaB. These inteins, DnaBi1 and DnaBi2, have homology to inteins in pathogens, splice with vastly varied rates, and are differentially responsive to environmental stressors. Whereas DnaBi1 splicing is reversibly inhibited by oxidative and nitrosative insults, DnaBi2 is not. Using a reporter that measures splicing in a native intein-containing organism and western blotting, we show that H2 O2 inhibits DnaBi1 splicing inM. smegmatis . Intriguingly, upon oxidation, the catalytic cysteine of DnaBi1 forms an intramolecular disulfide bond. We report a crystal structure of the class 3 DnaBi1 intein at 1.95 Å, supporting our findings and providing insight into this splicing mechanism. We propose that this cysteine toggle allows DnaBi1 to sense stress, pausing replication to maintain genome integrity, and then allowing splicing immediately when permissive conditions return. Inteins can act as post-translational environmental sensors in vivo. Here the authors characterize two inteins present in theMycobacterium smegmatis replicative helicase DnaB that display distinct splicing behaviors and are differentially sensitive to inhibition by biological stressors and propose that splicing inhibition could modulate DnaB levels to protect the cell against replication stress.